Предмет: Математика,
автор: аллленка2
помогите открыть скобки ((а-b ) -c)^2
Ответы
Автор ответа:
0
(а-b ) -c))^2 = (a - b - c)^2 = (a - b - c) * (a - b - c) =
= a^2 - ba - ca - ba + b^2 + bc - ca + bc + c^2 =
a^2 - 2ba + b^2 - 2ca + c^2 + 2 bc
= a^2 - ba - ca - ba + b^2 + bc - ca + bc + c^2 =
a^2 - 2ba + b^2 - 2ca + c^2 + 2 bc
Похожие вопросы
Предмет: Алгебра,
автор: vipnusratov
Предмет: Химия,
автор: uravorobov
Предмет: Алгебра,
автор: Alerdy
Предмет: Математика,
автор: костя20061
Предмет: Литература,
автор: asqwsa